2004
DOI: 10.2134/jeq2004.0882
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Sensitivity Analysis of Spatial Predictions of Heavy Metals in Wheat

Abstract: Heavy metals seriously threaten the health of human beings when they enter the food chain. Therefore, policymakers require precise predictions of heavy metal concentrations in agricultural crops. In this paper we quantify the uncertainty of regression predictions of Cd and Pb in wheat (Triticum aestivum L.) and the contributions to the uncertainties in these predictions associated with inputs to the regression model. For each node of the 500- x 500-m grid covering the arable soils in The Netherlands, a latin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Thus, the marginal distribution for each data series remains unchanged, but the correlations among the series are adjusted. The Iman and Conover (1982) method has been employed in a variety of practical applications; for example, see Maia and Neto (2004), Brus and Jansen (2004), and Wu and Tsang (2004).…”
Section: Programming For Whole-farm Insurancementioning
confidence: 99%
“…Thus, the marginal distribution for each data series remains unchanged, but the correlations among the series are adjusted. The Iman and Conover (1982) method has been employed in a variety of practical applications; for example, see Maia and Neto (2004), Brus and Jansen (2004), and Wu and Tsang (2004).…”
Section: Programming For Whole-farm Insurancementioning
confidence: 99%
“…soil properties and climatic data) (e.g. Diaz-Diaz and Loague, 2000), in pesticide properties (particularly the pesticide half-life and the coefficient for sorption on organic matter) (Boesten, 1991;Dubus et al, 2003), it can result from the use of imperfect pedotransfer functions (Tiktak et al 1999;Dubus et al, 2003) or be caused by spatial interpolation errors (Brus and Jansen, 2004). Model structure and the numerical solution of the model provide additional sources of uncertainty (Addiscott et al, 1995;Refsgaard et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, comparing the accumulation levels between two years, the HMs in both soil and rice plants increased significantly in the second year, especially for As, Cd, Cu and Zn. The observation that regular PBR fertilization resulted in increasing levels of HMs in soils and crops over time was also reported in some other areas (Brus and Jansen 2004;Hough et al 2004). Therefore, increasing HM accumulation in soil and crops caused by long-term PBR fertilization should be an important issue which needs very careful consideration.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, the HM levels in the PBR-fertilized soil were found to be within the Chinese soil quality standards (Chinese Environmental Quality Standard for Soils 1995) (Table 1) Table 2). There are many other studies also reporting that biogas slurry fertilization for vegetables, wheat (Triticum aestivum L.) or maize (Zea mays L.) did not result in excessive HM levels in food (Cheung and Wong 1983;Brus and Jansen 2004;Berenguer et al 2008;Islam et al 2010). However, the results of these studies, including the present one, do not imply that HMs in the PBR can be ignored during longterm PBR application.…”
Section: Discussionmentioning
confidence: 99%